(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
This article is devoted stylistic lexical-semantic information in mass. We consider the operation and the semantic content of the track as antyfrazys. Illustrative material Author determined primarily from the standpoint of stylistic expressiveness of language tools, including structural and semantic aspects.